HPMA-based polymeric conjugates in anticancer therapeutics. Issue 6 (June 2020) - Rani, Sarita; Gupta, Umesh
Highlights: HPMA (N-2-hydroxypropylmethacrylamide) is an emerging polymeric alternative for drug delivery applications. HPMA can be potentially conjugated to develop copolymers and HPMA-drug conjugates. Molecular weigh and polymeric architecture of HPMA is essential for selecting intended therapeutic applications. HPMA conjugates are efficiently applicable in anti-cancer drug delivery. Abstract : Polymer therapeutics has gained prominence due to an attractive structural polymer chemistry and its applications in diseases therapy. In this review, we discussed the development and capabilities of N -(2-hydroxypropyl) methacrylamide (HPMA) and HPMA–drug conjugates in cancer therapy. The design, architecture, and structural properties of HPMA make it a versatile system for the synthesis of polymeric conjugations for biomedical applications. Research suggests that HPMA could be a possible alternative for polymers such polyethylene glycol (PEG) in biomedical applications. Although numerous clinical trials of HPMA–drug conjugates are ongoing, yet no product has been successfully brought to the market. Thus, further research is required to develop HPMA–drug conjugates as successful cancer therapeutics.